Northern Goshawk sighting details contributed by Robert Walton, 1981 - Walton, Robertet al (1981)
Field notes written by Robert Walton detailing the sighting of a Northern Goshawk at Swiss Valley Nature Preserve in Dubuque County, IA on December 26, 1981. The bird was also seen between December 22 and 24, 1981. Epson - sheet feed